High-frequency scattering by objects buried in lossy media. - Bertoncini, F. (IEEE Transactions on antennas and propagation)
The uniform geometrical theory of diffraction (UTD) is extended so that it can be used to calculate the scattering from an object buried in a lossy medium. First, the accuracy of this high frequency method is examined by comparing numerical results for the scattering by a polygonal cylinder in a lossy medium of infinite extent with calculations based on a method of moments (MoM) solution. Next, the more difficult scattering problem of a polygonal cylinder in a lossy half space is treated. The UTD solution for the unbounded region is employed together with the fields of rays introduced by the interface between air and the lossy medium to obtain expressions for the scattered field in air and in the lossy medium